Down‐regulation of miRNA 145 and up‐regulation of miRNA 4516 may be associated with primary hypertension. Issue 11 (26th September 2019) - Özkan, Gülsüm; Ulusoy, Şükrü; Geyik, Elif; Erdem, Yunus
Abstract: Complex mechanisms including genetic factors have been proposed in the pathogenesis of primary hypertension (HT). Micro RNAs (miRNAs) are single‐stranded RNA molecules that are not converted into protein products. However, it has been established that genes regulate conversion into protein products. The primary aim of this study was to investigate the roles of miRNA 4516, miRNA 145, miRNA 24, and miRNA 181a in the pathogenesis of HT. The secondary aim was to investigate the relation between these miRNAs and renin, aldosterone, norepinephrine, renalase, and NOS. Fifty‐two hypertensive and 51 control normotensive individuals under observation in the Cappadocia cohort were included in the study. miRNA 4516, miRNA 181a, miRNA 24, and miRNA 145 levels were measured using the ddPCR method. miRNA 4516 and norepinephrine levels were significantly higher in the HT group ( P  < .005 for both), while miRNA 145 levels were significantly lower (<.05). miRNA 4516 up‐regulation ( P  < .05) and miRNA 145 down‐regulation ( P  < .05) were identified as independent predictors of HT. Renalase exhibited negative correlation with miRNA 4516 and positive correlation with miRNA 145 in the patient and control group. In addition, negative correlation was present between miRNA 24 and NE and NOS and between miRNA 181a and NOS in the patient group. Our study identified, for the first time in the literature, miRNA 4516 up‐regulation and miRNA 145 down‐regulation as independent determinants of HT. Further studies performed in the light of our findings may lead to a better understanding of the pathogenesis and new therapeutic possibilities.